Forensic-case analysis: from 3D imaging to interactive visualization - Urschler, Martin; Bornik, Alexander; Scheurer, Eva; Yen, Kathrin; Bischof, Horst; Schmalstieg, Dieter (IEEE computer graphics and applications, 2012)
An interactive framework prepares raw computed-tomography and magnetic-resonance-imaging scans for courtroom presentations. The framework makes use of combined computer graphics and computer vision techniques to enable a forensic case analysis workflow.